ʿIlm al-Aṣwāt (Phonetics and Phonology): Naẓariyyātuhu wa Taṭawwurātuhu wa Ahdāf Tadrīsihi - Rizki Widyanti (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2017)
Phonology is one of the most important branches of linguistic science, consisting of phonetics and phonology. Phonetics is the branch of linguistics that studies speech sounds from their physical and physiological aspects, including their production, articulation, transcription, and description. In contrast, phonology studies speech sounds from a functional perspective within the structure of a particular language, focusing on their properties, patterns, and semantic functions. Through phonology, we are able to identify and distinguish pronunciation units and describe various speech sounds and their characteristics. Since its emergence as a scientific discipline, phonology has maintained its focus on speech sounds as the primary medium of human communication. This article aims to discuss speech sounds in terms of their classifications and theoretical foundations, drawing on both classical and contemporary perspectives, including areas of scholarly disagreement. Furthermore, it explores issues in phonology such as the development of tone and intonation, with particular emphasis on the Arabic language.